Absorption, tissue distribution, and excretion of glycycoumarin, a major bioactive coumarin from Chinese licorice (Glycyrrhiza uralensis Fisch) - Ye, Linhu; Cheng, Lei; Deng, Yan; Wang, Sen; Wu, Xinyu; Ou, Shuiping; Chang, Qi; Zhao, Xinqian; Zhou, Wen; Yu, Jinghua; Wu, Zuqiang (Frontiers in Pharmacology, 2023)
Licorice (Glycyrrhiza uralensis Fisch) is a natural plant resource widely used as a food and herbal medication in China. Glycycoumarin (GCM) is a major coumarin in licorice that possesses several biological activities. However, little is known about its pharmacokinetic profile. The present study aimed to describe the oral absorption, tissue distribution, and excretion of GCM in rats. Free (parent drug) and/or total (parent drug plus the glucuronidated metabolite) GCM in biological samples was quantified before and after the hydrolysis reaction with β-glucuronidase using a reliable LC-MS/MS method. The results indicated that GCM was rapidly absorbed and transformed into its conjugated metabolites after administration. Free GCM plasma concentrations after i.v. (10 mg/kg) administration quickly decreased with an average t1/2,λz of 0.71 h, whereas the total GCM concentration reduced slowly with a t1/2, λz of 2.46 h. The area under the curve of glucuronidated metabolites was approximately four-times higher than that of free GCM. Presumably, because of hepatic and/or intestinal tract first-pass metabolism, GCM exhibited a poor bioavailability of 9.22%, as estimated from its total plasma concentration. Additionally, GCM was distributed rapidly and widely in various tissues except the brain. The liver had the highest concentration; further, GCM was promptly eliminated from test tissues after intraperitoneal (20 mg/kg) administration, but only a small amount of GCM was excreted via bile and urine. Overall, GCM is absorbed and rapidly transformed into its conjugated metabolites with low bioavailability; further, it is distributed in various tissues, except the brain. These pharmacokinetic results are helpful for better understanding the characteristics and pharmacological effects of GCM.